IMPLEMENTASI KEPEMIMPINAN PROFETIK DI PONDOK PESANTREN MADRASAH TARBIYAH ISLAMIYAH (MTI) CANDUANG - Yanti, Ira; Sumarni, Weni; Simbolon, Ali Mustopa Yakub; Aldri, Aldri; Iswantir, Iswantir (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2023)
This research study was structured to describe and examine Buya Anas Khatib Bandaro's prophetic leadership at the Islamic Tarbiyah Islamic Boarding School (MTI) Canduang. The approach used is descriptive qualitative by collecting data in the form of interviews, observation and documentation. The research subject was Rais Al-Madrasah of the Islamic Tarbiyah Islamic Boarding School (MTI) Canduang. Based on the research results, the pesantren under the leadership of Buya Anas Khatib Bandaro has distinctive characteristics in accordance with the principles of the Prophet (Prophetic Leadership) in leading. This can be seen from the way he leads the MTI Canduang Islamic Boarding School, namely deciding policies based on Istiqamah, Mahabbah, Keshalehan, Siddiq, Amanah, Tabligh and Fathanah. In addition, there are supporting factors for this leadership, such as the support from the family of the founder of the Islamic boarding school, alumni and the local government. However, there is still a lack of support from the local community for the development of Islamic boarding schools.